Review of the Multimedia companion to The Middle Palaeolithic site of Combe-Capelle Bas (France), by H. L. Dibble and S. P. McPherron. [CD-ROM] - Paul Pettitt (Internet Archaeology, 1998)
It is quite ironic that, as an archaeologist concerned with ancient (lithic) technology, I should be so ignorant about recent advances in modern technology, particularly in the field of information technology which is having such a profound effect on the nature of academic disciplines. It was therefore with some trepidation that I undertook to review the CD-Rom companion to a recent publication in Palaeolithic archaeology (Dibble, H. L. and Lenoir, M. 1996), and user-friendliness, I thought, would be the primary criterion on which, for me, the CD would stand or fall.